Association Analysis of Seagrass Coverage and Human Activities in Nusa Lembongan - Wardono, Suko; Sobhytta, Elland Yupa; Dhananjaya, I Gusti Ngurah Agung; Lasniroha, Rodo; Pumpun, Yuniarti Karina; Mashuda, Mochammad Miftakhul; Saputra, Dewa Gde Tri Bodhi; Yudiarso, Permana (UIN Sunan Gunung Djati Bandung, 2022)
Nusa Lembongan has high marine biodiversity, including seagrass. Seagrass is a plant that lives submerged in a marine or estuary water that functions as a nursery ground, trapping sediment, and beach protector, so it is important to know the condition of seagrass coverage, especially in Nusa Lembongan for managing the Nusa Penida Marine Protected Area. This study aimed to understand the condition of seagrass coverage and the factors influencing the existence of its ecosystem in Nusa Lembongan. According to reslut in two stations, it was found that six of the twelve types of seagrasses in Indonesia, namely Enhalus acoroides, Thalassia hemprichii, Cymodocea serrulata, Cymodocea rotundata, Halodule pinifolia, and Halophila ovalis. From the two stations (LMB01 and LMB02), the total seagrass coverage was 38.10Â±30.98% or the medium category. The seagrass communities in the station areas were generally formed by 3 types of seagrasses; Thalassia hemprichii, Cymodocea serrulata, and Cymodocea rotundata. LMB02 has higher seagrass coverage than LMB01. The seagrass coverage is inversely proportional to the intensity of human activity.